Nanoplasmonic‐Enhanced Spintronic Terahertz Emission. Issue 2 (28th November 2021) - Liu, Shaojie; Guo, Fengwei; Li, Peiyan; Wei, Gaoshuai; Wang, Chun; Chen, Xinhou; Wang, Bo; Zhao, Weisheng; Miao, Jungang; Wang, Li; Xu, Yong; Wu, Xiaojun
Abstract: Recently fashionable spintronic terahertz (THz) emission provides fresh pathways for contactless diagnosing femtosecond spin currents, opens the door for developing next‐generation high‐performance THz emitters, and accelerates the interdisciplinary of ultrafast THz optospintronics. However, one of the research highlights of ultrafast magnetism and the difficulty for further improving the spintronic THz emission productivity is how to efficiently reduce the energy consumption of all‐optical magnetitic manipulation and improve the optical spin injection efficiency. Here, it is demonstrated, for the first time, gold nanorods (GNRs) plasmonic resonances can effectively increase the THz emission from W/CoFeB/Pt heterostructures by 140%. Systematic investigations of THz yield dependences on pumping laser incidence directionality, polarization, and the GNRs dimension parameter conclusively manifest the surface plasmon resonance validity. Theoretical interpretations combined with Drude–Lorentz model and numerical simulations semiquantitatively reproduce the experimental results. The observations prove that THz efficiency can be improved by nanophotonic technologies and may also spark inspiration for developing functional nano‐THz optospintronic devices. Abstract : It is demonstrated, for the first time, that nanoplasmonic resonance can effectively enhance the spintronic terahertz radiation from W/CoFeB/Pt heterostructures by 140%. The gold nanorods enhanced spintronic terahertz emission properties are systematically investigated through varying the laser incidence direction, polarization, and the gold nanorods dimension. Theoretical interpretations combined with Drude–Lorentz model and numerical simulations semiquantitatively reproduce the experimental results.